Laporan Kasus: Perimortem Sectio Caesarean pada Ibu Hamil dengan Henti Jantung - Yanti Permatasari; Willy Yant Kartolo (Intisari Sains Medis, 2018)
Background Perimortem caesarean section (PMCS) was done in pregnant women with no hope for survival, and not responding to initial resuscitative maneuver. The primary aim of PMCS procedure is to empty the uterus to aid maternal resuscitation.Case Presentation We performed a PMCS after no response of cardiopulmonary resuscitation (CPR) in a 19 years old woman with severe preeclampsia, severe anemia, and acute lung edema.ConclusionThis is a case report of PMSC procedure performed in maternal cardiac arrest. The PMCS was done after no response of CPR with left uterine displacement (LUD). However, the outcome of maternal and neonatal deaths was unavoidable.